Endophytic Bacteria Isolated from Citrus Plants for Biological Control of Citrus Canker in Lime Plants - Orawan Daungfu,; Somchit Youpensuk,; Saisamorn Lumyong, (Tropical Life Sciences Research, 2019)
Citrus canker caused by Xanthomonas citri subsp. citri is a disease affecting the yield and fruit quality of lime (Citrus aurantiifolia). This research investigated endophytic bacteria obtained from six healthy Citrus spp. to inhibit the pathogen and to control citrus canker on lime plants. Numbers of the endophytic bacteria isolated from C. aurantifolia, C. hystrix, C. maxima, C. nobilis, C. reticulata and C. sinensis were 28, 25, 29, 42, 12 and 34 isolates, respectively. The selected endophytic bacteria that were effective against X. citri subsp. citri were Bacillus amyloliquefaciens LE109, B. subtilis LE24 and B. tequilensis PO80. The optimum culture medium for an antagonistic effect on the pathogen in B. amyloliquefaciens LE109 and B. tequilensis PO80 was yeast extract peptone dextrose broth, and in B. subtilis LE24 was modified soluble starch broth. To control citrus canker in lime, young expanded leaves of lime plants were aseptically punctured and inoculated with 30 ?l of bacterial suspension of the pathogen (108 CFU/ml in 0.85% NaCl) per punctured location. After the pathogenic inoculation for 24 h, the leaves were then inoculated with 30 ?l of the selected endophytic bacteria (108 CFU/ml in 0.85% NaCl), and treated with 30 ?l of the culture media containing bioactive compounds produced by the selected endophytic bacteria. The leaves inoculated with cell suspensions of B. amyloliquefaciens LE109 or B. subtilis LE24 could completely control citrus canker. However, the leaves inoculated with B. tequilensis PO80 displayed 10% disease incidence. Additionally, the leaves treated with the crude bioactive compounds of B. amyloliquefaciens LE109 or B. subtilis LE24 could completely control citrus canker. Notably, the leaves treated with the crude bioactive compounds of B. tequilensis PO80 displayed 5% disease incidence. The results of this study showed that the Bacillus strains play important roles in the biocontrol of citrus canker in lime.